PURCHASE DECISION BASED ON THE BRAND IMAGE, PRODUCT DESIGN AND LIFESTYLE ON CONVERSE SHOES IN SURAKARTA - Assa Agustin; Sudarwati Sudarwati; Siti Maryam (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The purpose of this study was to determine the effect of brand image, product design and lifestyle on purchasing decisions for Converse shoes in Surakarta. This type of research uses quantitative descriptive research. The variables in this study were a brand image, product design and lifestyle. The population of this study was all people of Surakarta City, especially those who wear Converse shoes. The research sample consisted of 100 people, using purposive sampling technique, and data collection using a questionnaire. The data analysis technique used in this research is the coefficient of determination analysis technique, the classical assumption test and multiple linear regression. The test results of multiple linear regression analysis show that brand image has no significant effect on purchasing decisions, product design has a significant effect on purchasing decisions, and lifestyle has a significant effect on purchasing decisions. Keywords: Brand.Image, Product.Design,.Lifestyle